2013
DOI: 10.1038/onc.2013.365
|View full text |Cite
|
Sign up to set email alerts
|

The MutSβ complex is a modulator of p53-driven tumorigenesis through its functions in both DNA double-strand break repair and mismatch repair

Abstract: Loss of the DNA mismatch repair protein MSH3 leads to the development of a variety of tumors in mice without significantly affecting survival rates, suggesting a modulating role for the MutSβ (MSH2-MSH3) complex in late onset tumorigenesis. To better study the role of MSH3 in tumor progression, we crossed Msh3−/− mice onto a tumor predisposing p53-deficient background. Survival of Msh3/p53 mice was not reduced compared to single p53 mutant mice; however, the tumor spectrum changed significantly from lymphoma t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…Loss of MSH3 leads to a decrease in expansion events and promotes contractions. However, disruption of Msh2-Msh3 will have a negative impact on overall genome stability; in addition to MMR, Msh2-Msh3 has been implicated in DSBR (Surtees et al 2004;Park et al 2013;van Oers et al 2013) and interstrand DNA cross-link repair (Takahashi et al 2011;Barber et al 2005;Zhao et al 2009). Notably, many neuronally expressed genes contain repetitive sequences in their regulatory regions (Bacolla et al 2008), the stability of which is likely at least partially dependent on Msh2-Msh3.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of MSH3 leads to a decrease in expansion events and promotes contractions. However, disruption of Msh2-Msh3 will have a negative impact on overall genome stability; in addition to MMR, Msh2-Msh3 has been implicated in DSBR (Surtees et al 2004;Park et al 2013;van Oers et al 2013) and interstrand DNA cross-link repair (Takahashi et al 2011;Barber et al 2005;Zhao et al 2009). Notably, many neuronally expressed genes contain repetitive sequences in their regulatory regions (Bacolla et al 2008), the stability of which is likely at least partially dependent on Msh2-Msh3.…”
Section: Discussionmentioning
confidence: 99%
“…In response to ionizing radiation, G2/M checkpoint activation in Msh2 À/À cells is inefficient, such that the cells arrest only transiently before progressing into mitosis (Franchitto et al, 2003). More recently, it has been shown that Msh2 À/À and Msh3 À/À , but not Msh6 À/À , mouse embryonic fibroblasts display a significant increase in chromatid breaks compared to wild-type cells, indicating a defect in DSB repair due to loss of MutSb function (van Oers et al, 2014). However, the role of MutSb in the cellular response to DSBs remains largely uncharacterized.…”
Section: Introductionmentioning
confidence: 97%
“…1-4 ). There is accumulating circumstantial evidence suggesting a role for the MSH2-MSH3 complex in DSB repair (39)(40)(41)(42)(43). For instance, RNAi-mediated MSH3 depletion has recently been shown to result in substantially delayed RAD51 loading after 2-Gy ionizing radiation ( 25 ).…”
Section: Alterations In Homologous Recombination Signaling Are Associmentioning
confidence: 99%